Peran Guru sebagai Street-Level Bureaucrat dalam Mendukung Kebijakan Pendidikan Berbasis Digital di SMA Negeri 5 Kupang - Oktavianus Nuwa; Mariayani Oktafiana Rene (Jurnal Administrasi Publik, 2023)
The purpose of this study is to identify and explain how teachers, as street-level bureaucrats, carry out their roles in supporting the implementation of digital-based learning programs at SMA Negeri 5 Kupang. This research was conducted using a descriptive-qualitative approach. Data collection was conducted through in-depth interviews, a literature study, and field observation. The results showed that teachers of SMA Negeri 5 Kupang, as street level bureaucrats, carry out five roles to support the implementation of digital-based learning programs, namely: (1) mentors, as alternative providers in solving problems related to the use of digital media, as curriculum providers, and as innovators; (2) mentors, as teachers in the operation of hardware, software, and applications applied in digital-based learning, and as advisors; (3) motivators, motivating students to think critically in the use of digital media, appreciating, and improving students' skills; (4) facilitator, providing access to the use of digital technology, providing project- or task-based learning, facilitating online discussion, and building communication with parents; (5) demonstrator, showing students how to use digital media effectively and efficiently, providing examples, and demonstrating how to solve technical problems; and (6) evaluator, assessing students' progress in the application of digital technology and assessing the safety of the application of digital technology. The results also show that in carrying out this role, SMA Negeri 5 Kupang teachers are still faced with several obstacles, such as limited resources, financial constraints, limited knowledge and skills, the digital divide, a lack of awareness related to digital ethics, a lack of student involvement and motivation, limited subjectivity, observation difficulties, and the complexity of digital security.